Slow and fast cortical cholinergic arousal is reduced in a mouse model of focal seizures with impaired consciousness - Lim-Anna Sieu; Shobhit Singla; Jiayang Liu; Xinyuan Zheng; Abdelrahman Sharafeldin; Ganesh Chandrasekaran; Marcus Valcarce-Aspegren; Ava Niknahad; Ivory Fu; Natnael Doilicho; Abhijeet Gummadavelli; Cian McCafferty; et al. (Cell Reports)
Summary: Patients with focal temporal lobe seizures often experience loss of consciousness associated with cortical slow waves, like those in deep sleep. Previous work in rat models suggests that decreased subcortical arousal causes depressed cortical function during focal seizures. However, these studies were performed under light anesthesia, making it impossible to correlate conscious behavior with physiology. We show in an awake mouse model that electrically induced focal seizures in the hippocampus cause impaired behavioral responses to auditory stimuli, cortical slow waves, and reduced mean cortical high-frequency activity. Behavioral responses are related to cortical cholinergic release at two different timescales. Slow state-related decreases in acetylcholine correlate with overall impaired behavior during seizures. Fast phasic acetylcholine release is related to variable spared or impaired behavioral responses with each auditory stimulus. These findings establish a strong relationship between decreased cortical arousal and impaired consciousness in focal seizures, which may help guide future treatment.